PENGARUH RETRIBUSI PARKIR, RETRIBUSI TERMINAL DAN RETRIBUSI PENGUJIAN KENDARAAN BERMOTOR TERHADAP BELANJA LANGSUNG (Studi Pada Dinas Perhubungan, Komunikasi dan Informatika Kota Palu) - Hudayah, Husnul (Katalogis, 2017)
This research is aimed to determine and analyze the impact of Parking Retributions, Terminal Retributions and Vehicle Inspection Retributions on Direct Expenditure in The Department of Transportation, Communications and Informatics, Palu City. Population covers the entire element in The Department of Transportation, Communicaion and Informatics Palu City. Data is analyzed with multiple linier regression with a confidence level of 95% and significance level of 5%. The result of the test explains that Parking Retributions (X1), Terminal Retributions (X2) and Vehicle Inspection Retributions (X3) simultaneously have significant impact on Direct Expenditure (Y). the value of correlation coefficient (Multiple R) is 0.566 or 56.6%, determinant coefficients (R square) is 0.320 or 32.0% and adjusted R square is 0.265 or 26.5. partially, Parking Retributions impacts the direct expenditure with significant value of 0.004, Terminal Retributions of 0.401, and Vehicle Inspection Retributions of 0.784.these result imply that Terminal and Vehicle Inspection Retributions partially have insignificant impact on Direct Expenditure in The Department of Transportation, Communication and Informatics of Palu City.